The results of the study of agricultural technology sustainable white wine grapes for a new generation of biological wines production - Vladislav V. Fadeev; Agamagomed K. Radzhabov; Vasily I. Demenko (Овощи России, 2019)
Relevance. Widely used traditional wine varieties of European-Asian grapes are characterized by a low level of resistance to disease and require multiple treatments with pesticides to preserve the crop and plants. Obtaining and introduction of sustainable varieties into production is one of the urgent problems of modern viticulture in the world and in our country, especially in the aspect of the ever wider dissemination of the principles of organic production. This is especially true for vineyards located in the coastal areas of the South of Russia, where the use of methods of chemical protection of vineyards from pests and diseases are limited to the proximity to the sea coast and the status of the resort region.Material and methods. The paper presents the results of the study of white wine grapes of the new generation with a high potential for resistance to environmental conditions and diseases. Purpose: research and development of recommendations on the use of white wine grapes of the new generation, characterized by resistance to adverse environmental conditions.Results. It is revealed that the experimental white wine varieties are characterized by a high level of adaptive capacity. In terms of productivity, new varieties are not inferior to the Sauvignon variety. Wine materials made from new resistant varieties are characterized by a high content of extractive and phenolic compounds. According to the organoleptic characteristics of wine materials from new resistant white grape varieties are at the level of the control variety. It is established that the level of stability of new grape varieties can be excluded from the technology of care of the vineyard measures to protect against major diseases, which significantly reduces the cost of production and allows you to get environmentally safe and organic products.